2016
DOI: 10.1002/jts.22139
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sleep Disturbance on Global Functioning After Posttraumatic Stress Disorder Treatment

Abstract: Chronic insomnia and recurrent nightmares are prominent features of posttraumatic stress disorder (PTSD). Evidence from adult research indicates that these sleep disturbances do not respond as well to cognitive-behavioral therapies for PTSD and are associated with poorer functional outcomes. This study examined the effect of prolonged exposure therapy for adolescents versus client-centered therapy on posttraumatic sleep disturbance, and the extent to which sleep symptoms impacted global functioning among adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 42 publications
4
17
1
Order By: Relevance
“…Regarding the temporal association between sleep disturbance and PTSD severity, studies have supported similar effects of sleep disturbance on PTSD symptomatology, as reported in the current study in both civilian and military populations (Breslau et al, 2004;Miller et al, 2017). It has also been proposed that treating sleep problems directly is beneficial for both civilians and military populations with PTSD (Brownlow, Harb & Ross, 2016;Koffel et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding the temporal association between sleep disturbance and PTSD severity, studies have supported similar effects of sleep disturbance on PTSD symptomatology, as reported in the current study in both civilian and military populations (Breslau et al, 2004;Miller et al, 2017). It has also been proposed that treating sleep problems directly is beneficial for both civilians and military populations with PTSD (Brownlow, Harb & Ross, 2016;Koffel et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…Our longitudinal data suggest a causal pathway between sleep disturbance severity at T1 and severity of both sleep-related and non-sleep-related symptoms at T2 in addition to a positive, although weaker, association between PTSD symptom count at T1 and sleep problem frequency at T2. Given the frequency of sleep disturbance complaints in our cohort overall, insomnia is an obvious, high-value target for intervention in veterans with PTSD (Brownlow et al, 2016;Taylor et al, 2018). Our findings have similar implications for clinicians treating PTSD symptoms in nonmilitary populations given growing evidence of a similar association between sleep disturbances and PTSD severity for individuals being treated in other settings or with non-military-related traumatic memories (Cox et al, 2017;Miller et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Only a small number of studies have investigated the effects of trauma-focused PTSD therapies on sleep outcomes ( Belleville et al., 2011 , Brownlow et al., 2016 , Galovski et al., 2009 , Galovski et al., 2016 , Gutner et al., 2013 , Levrier et al., 2016 , Lommen et al., 2015 , Nishith et al., 2003 , Raboni et al, 2006 , Zayfert and DeViva, 2004 ). Improvement in sleep has been found for prolonged exposure (PE) and cognitive processing therapy (CPT) for PTSD ( Brownlow et al., 2016 , Galovski et al., 2016 , Galovski et al., 2009 , Gutner et al., 2013 ), eye-movement desensitization and reprocessing therapy ( Raboni et al., 2006 ), other cognitive behavioural therapies ( Belleville et al., 2011 , Levrier et al., 2016 , Nishith et al., 2003 , Zayfert and DeViva, 2004 ), and cognitive therapy for PTSD (CT-PTSD) ( Lommen et al., 2015 ). Direct comparisons of two evidence-based, trauma-focused PTSD therapies, CPT and PE, found no differences in sleep improvement between treatments ( Galovski et al., 2009 ; Gutner et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However there are persisting concerns about this modality due to high rates of non-response and dropout [35]. Moreover, sleep disturbance is a core feature of PTSD [6] and a predictor of worse global functionality [7], yet sleep improvement is typically elusive after completion of PTSD-specific behavioral therapies [8, 9]. While SSRI and other medication prescriptions are common, the overall evidence for the efficacy of psychopharmacological agents for individuals with PTSD is generally considered to be modest at best [1, 10].…”
Section: Introductionmentioning
confidence: 99%